Selection and roles of scientific editors and editorial boards - the Malaysian experience. - Chin, H. F.; Pillai, Sumangala (1988)
Scientific editors are a specialized group of editors who are usually attached to research institutes, centres of higher learning and professional societies. Unlike general editors, scientific editors prepare technical information for dissemination to a specialized audience. Selection of scientific editors and editorial boards in Malaysia is mainly based on the scope and policy of the journal that it will serve. In the selection of scientific editors either by the Chief Editor or the management, the following qualities or characteristics are looked for : (i) objectivity (ii) research experience and involvement (iii) contacts with researchers in identical fields (iv) resourcefulness (v) dedication and (vi) time for board meetings and activities. For a very specialized journal, the Editorial Board may be small with the members being chosen to represent each area of specialization. Sometimes they themselves may serve as referees to the articles received. On the other hand, the Editorial Board members of a very diverse journal like UPM's journal, PERTANIKA, receive and appraise articles. They do not usually referee but instead identify referees for each paper received. This is to ensure impartiality as well as to maintain research excellence. The Editorial Board collectively rejects or accepts papers for publication. In its decision to accept a paper, it has to ensure that it is within the scope and policy of the journal. The Editorial Board also plays the unenviable role of a 'middleman' between the authorities on one part and the authors, referees, printers, subscribers and readers on the other part to ensure the timely production of the journal in an efficient and resourceful manner. Finally, the Editorial Board ensures the dissemination of the journal to most of its target audience.